Nida Blanca: Noon hanggang ngayon was named video of the year - Liamzon, Jojo (Animo Repository, 1988)
Nida Blanca: Noon Hanggang Ngayon, a documentary produced by Com-Arts majors, Jojo Liamzon and Poi Tandoc, was named Video of the Year at the 1988 Amateur Video Art Competition held in conjunction with the U.P. Fine Arts Week. The competition was participated in by students and independent video makers from all over the Philippines.